Gibraltar in the sixties: British, Spanish and local interests on the Rock - Szente-Varga, Mónika (Études sur la Région Méditerranéenne, 2012)
300 years ago, in 1713, Gibraltar was ceded to the British by the Treaty of Utrecht. And for 300 years long, the Spanish have been trying to get it back, using diplomatic and/or military means. This study investigates a 10-year period of intensive pressure making - the 1960’s - principally with the help of the ABC, a Spanish daily, and a report made in 1969 by Jenő Incze, the Hungarian ambassador in London. The essay is complemented by details on the actual situation of Gibraltar. The sixties could become a period of intensive diplomatic activity due to the reincorporation of Spain into the international community in the 1950’s. Spain, that had been considered as a pariah state since the Allied victory in the Second World War - the United Nations for example called on its members to withdraw their ambassadors from Madrid - was now accepted due to its militant anti-communism. The bipolar world was morally divided into bad and good, that is, into Communists and anti-Communist, and much less consideration was given to democratic institutions. Thus the Cold War ended the isolation of Spain: diplomatic and communication channels were reopened and it could make its comeback on the international scene. For example, diplomatic relations were restored between Spain and Great Britain in 1951; Spain and the United States signed an agreement on military cooperation in 1953; the same year a concordat was reached with the Vatican, and in December 1955 Spain finally became a member of the United Nations. The Spanish leadership did not wait long, and as early as 1957, it announced its claim onto Gibraltar.